PENGARUH N-ASETIL SISTEIN ORAL TERHADAP PENURUNAN HsCRP PADA PASIEN PENYAKIT GINJAL KRONIS STADIUM V YANG MENJALANI CONTINUOUS AMBULATORY PERITONEAL DIALYSIS (CAPD) - Nurhayatun, Evi (Biomedika, 2019)
Inflammation and oxidative stress are risk factors of cardiovascular diseases among chronic kidney disease patients. There is increasing of HsCRP level in stage V CKD patients wih CAPD. N-Acetyl Cysteine(NAC) is a compounds containing thiol with antioxidant and anti-inflammatory effects. This research obejectives was to examine the effect of oral NAC in the decline of HsCRP level in stage V CKD patients with CAPD. This is an experimental research with Randomized Double Blind Control Trial, involving 30 patients CKD with CAPD Dr Moewardi Hospital and complete inclusion and exclusion criteria, divided 15 patients as a control group (placebo) and 15 patients as a treatment group of oral NAC. Examination of data research variables have been performed before and after 8 weeks treatment. The results were the level of HsCRP in control group before treatment and after treatment (15,76±42,79 vs 16,50±30,63). Level of HsCRP in treatment group before treatment and after treatment (29,53±76,52 vs 4,56±12,85) was decrease statistically significant with p< 0,05. The N-Acetyl Cysteine orally can decreased the level of HsCRP in stage V CKD patients with CAPD.Keywords : N-Acetyl Cysteine, CAPD, HsCRP